Autumn staging of Cackling Canada Geese on the Alaska Peninsula - Sedinger, James S; Bollinger, Karen S (Wildfowl, 1987)
Cackling Canada Geese Branta canadensis minima undergo a long (2,800 km) migration between their autumn staging areas on the Alaska Peninsula and wintering areas in Oregon and California. Adults and young lost an average of 543 g during this migratory flight. Weight gains between fledging and autumn migration are essential for the successful completion of the flight. Autumn staging is important for the acquisition or maintenance of energy stores, particularly for young of the year, as evidenced by the intense feeding of this age class at Ugashik Bay. Factors associated with the arrival and departure of Cackling Geese at Ugashik Bay are presently unknown.